2010
DOI: 10.1002/jsfa.4178
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties of patatin gels compared with β-lactoglobulin, ovalbumin, and glycinin

Abstract: Patatin was found to form gels with comparable small-deformational rheological properties as typical food proteins. In addition, at concentrations where the elastic modulus was similar for all proteins, the frequency and strain dependence were also comparable. From this it is concluded that patatin is a promising protein to be used in food applications as a gelling agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 46 publications
(58 reference statements)
6
65
0
1
Order By: Relevance
“…In fact, galloylated proanthocyanidins are removed in a preferential way [17]. Moreover, hydrophobic interactions could be mainly responsible for precipitation by vegetal proteins derived from pea and potato, and some studies have confirmed the relatively high surface hydrophobicity of patatin [17,27].…”
Section: Total Phenolic Compounds and Flavanolsmentioning
confidence: 99%
“…In fact, galloylated proanthocyanidins are removed in a preferential way [17]. Moreover, hydrophobic interactions could be mainly responsible for precipitation by vegetal proteins derived from pea and potato, and some studies have confirmed the relatively high surface hydrophobicity of patatin [17,27].…”
Section: Total Phenolic Compounds and Flavanolsmentioning
confidence: 99%
“…Disulphide bonding may only be achievable when the molecules are in a particular orientation close to each other, or already high molecular aggregates exist [14]. Creusot et al [50] also reported an unusually high exposed hydrophobicity of patatin during the unfolding of the tertiary structure.…”
Section: Effects Of Eg and Pgmentioning
confidence: 99%
“…As a result, native potato protein has recently become commercially available. These protein preparations are used as foaming- [7] and gelling agents [8] and as emulsifiers [9], while still retaining their bioactive properties.…”
Section: Introductionmentioning
confidence: 99%